Between images and the process of making see: research on the Mebengokré-Xikrin figurative drawings from the Lux Vidal collection - Baumgaertner, Mariana Floria (GIS - Gesture, Image and Sound - Anthropology Journal, 2023)
The Mebengokré-Xikrin drawings, collected by the anthropologist Lux Vidal between the 1970s and 1980s, were made by different people of different ages, mostly men who had never drawn before. They express human forms, animals, villages and mythical events, but also the construction of the relationship between the anthropologist and her interlocutors. They are spontaneous productions that, continually (re)visited, evoke narratives that would not be possible otherwise. Relationships, interpretations and memories are continually updated by (re)seeing and (re)accessing, where the act of archiving results in continuous processes of constituting and ordering knowledge, from collection to organization and uses.This work is the result of scientific initiation research, developed between 2019-2020, which aimed to research and document 431 figurative drawings, housed in the Laboratório de Imagem e Som em Antropologia (LISA), at the University of São Paulo.